Pengembangan Media Berbasis Website Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Sumber dan Bentuk Energi - Saidah, Lathifatus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Learning media that is less interesting and does not suit students' conditions is one of the learning problems in the classroom. This research explains the process of developing website-based learning media, the validity of website-based learning media, and the effectiveness of website-based learning media on student learning outcomes. The research was conducted at MI Al Ma'arif 07 Singosari. The research subjects were 20 third-grade students. The product resulting from this research is website-based learning media that focuses on source materials and forms of energy. This research uses the ADDIE research and development model. The percentage score from the validation of learning media is 93.3. Meanwhile, the percentage score from material validation was 90.67. Furthermore, the results of testing the product that has been developed received a percentage score of 85. Thus, website-based learning media is very effective and worthy of being tested on source materials and forms of energy.